Development of Cash and Operational Expenditure Reconciliation Information System for Official Financial Management with Agile Methods - Maulana, Muhammad Sony; Ali Mustopa; Agung Sasongko; Ravi Manisha; Steven (Yayasan Cendekiawan Digital Indonesia (CEDDI), 2025)
Government agencies often encounter challenges in enhancing the efficiency and accuracy of financial report management, particularly in the cash reconciliation process. This study, conducted at the Regional Financial and Asset Management Agency (BPKAD) of Mempawah Regency, addresses the inefficiencies of traditional reconciliation methods that require face-to-face interactions and up to two working days to complete. The research aims to develop the Official Cash and Operational Expenditure Information System (SIKASBON) using the Agile methodology, enabling a more responsive, flexible, and user-oriented financial data synchronization process. The system was developed through a structured approach involving requirement analysis, design, development, testing, deployment, and review. System evaluation using the System Usability Scale (SUS) yielded an impressive average score of 85.2, categorized as A+ (Best Imaginable). The findings demonstrate that SIKASBON significantly improves transparency and efficiency in managing cash and operational expenditures. Most notably, the time required for reconciliation was reduced from two working days to just 10 minutes. This research contributes to the digital transformation of public financial management by offering a scalable solution that aligns with user needs and promotes accountability in government operations.